Acute hepatitis B in the era of immunisation: pitfalls in the identification of high risk patients. Issue 965 (3rd March 2006) - Rosner, G; Lurie, Y; Blendis, L; Halpern, Z; Oren, R
Abstract : Background: Since the adoption of a universal hepatitis B immunisation strategy, the reported incidence of acute hepatitis B has declined dramatically worldwide including in Israel. However, new cases of acute hepatitis B still occur. The aim of this study was to describe the incidence of acute hepatitis B in a referral area, routes of transmission, and outcome. Methods: The charts of all new hepatitis B patients, who visited the clinic in the years 2002 and 2003 (January 2002 to December 2003), were reviewed. The main criteria for a diagnosis of acute hepatitis B were transient increase of alanine transaminase activity, and hepatitis B surface antigen seroconversion. Results: Twenty nine men and seven women were diagnosed with acute hepatitis B infection during the study period. Two patients were previously vaccinated with hepatitis B vaccine. One case of hepatitis D coinfection was reported. The incidence of acute hepatitis B in the referral area was estimated as 2.25 per 100 000 adult population. Mean age was 36 years (17–75). Twenty one patients (18 men and 3 women) acquired the virus through unprotected sexual contact, and seven patients through iatrogenic exposure. Thirty three patients underwent spontaneous seroconversion while three patients became chronic carriers. Conclusions: Despite a universal immunisation policy, frequent cases of acute hepatitis B in Israel are still seen. High risk heterosexual activity and iatrogenic exposure seem to be the commonest routes of transmission. Further recommendations regarding vaccination policy are discussed.